O Uso de Recursos Estratégicos na Produção de Orgânicos: O Caso dos Produtores da Feira Ecológica de Passo Fundo-RS - Ana Claudia Machado Padilha (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
The research aims to identify the tangible and intangible resources that are configured as strategic in the organic production of the farmers of the Passo Fundo-RS Ecological Fair. Methodologically, an exploratory and qualitative research was carried out, with the target population being the organic producers of the Passo Fundo Ecological Fair, six producers were surveyed using the saturation criterion based on selection criteria that answered the questionnaire, from the Resource Based View (RBV) literature that were analyzed using the content analysis technique. As significant results, it can be highlighted that tangible and intangible resources are fundamental elements for the success of the organic production activity, with special emphasis on the cooperative institution that has the function of assembling the producers, making feasible the commercialization channel and, especially, to offer certification mechanisms for organic production.